Frontal lobe hemodynamics detected by functional near-infrared spectroscopy during head-up tilt table tests in patients with electrical burns - Kim, Yoo Hwan; Kim, Youngmin; Yoon, Jaechul; Cho, Yong Suk; Kym, Dohern; Hur, Jun; Chun, Wook; Kim, Byung-Jo (Frontiers in Human Neuroscience, 2022)
Significance: Electrical burns can cause severe damage to the nervous system, resulting in autonomic dysfunction with reduced cerebral perfusion. However, few studies have investigated these consequences. Aim: To elucidate changes in prefrontal cerebral hemodynamics using functional near-infrared spectroscopy (fNIRS) during the head-up tilt table test (HUT) for patients with electrical burns. Approach: We recruited 17 patients with acute electrical burns within 1 week after their accidents and 10 healthy volunteers. The NIRS parameters acquired using an fNIRS device attached to the forehead were analyzed in five distinct HUT phases. Results: Based on their HUT response patterns, patients with electrical burns were classified into the group with abnormal HUT results (APG, n=4) or normal HUT results (NPG, n=13), and compared with the healthy control (HC, n=10) participants. We found trends in hemodynamic changes during the HUT that distinguished HC, NPG, and APG. Reduced cerebral perfusion and decreased blood oxygenation during the HUT were found in both the NPG and APG groups. Patients with electrical burns had autonomic dysfunction compared to the HC participants. Conclusions: Using fNIRS, we observed that acute-stage electrical burn injuries could affect cerebral perfusion.